1993
DOI: 10.1136/hrt.69.5.391
|View full text |Cite
|
Sign up to set email alerts
|

Anticardiolipin antibodies in ischaemic heart disease: marker or myth?

Abstract: Objectives-To assess the incidence and significance of anticardiolipin antibodies after myocardial infarction and in unstable angina.Design-A prospective study of all patients under 60 admitted to the coronary care unit over a 12 month period with a diagnosis of acute myocardial infarction who were followed up for a further 12 months. Patients admitted with unstable angina were similarly assessed but not followed up. Anticardiolipin antibody concentrations were compared with those of age matched controls.Setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
20
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 6 publications
5
20
0
Order By: Relevance
“…In 597 acute MI survivors, Sletnes, et al 20) using multivariate analysis, failed to prove that aCL is an independent risk for mortality, cerebral thromboembolism, or recurrent MI. Similar results were obtained by Cortellaro, et al 22) in their study of 74 young MI patients and Phadke, et al 5) who measured aCL in 299 survivors of acute MI. Zuckerman, et al 4) reported that the rates of thromboembolic events and myocardial reinfarction in patients with acute MI were significantly higher in aCL-positive patients than in the aCL negative group.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In 597 acute MI survivors, Sletnes, et al 20) using multivariate analysis, failed to prove that aCL is an independent risk for mortality, cerebral thromboembolism, or recurrent MI. Similar results were obtained by Cortellaro, et al 22) in their study of 74 young MI patients and Phadke, et al 5) who measured aCL in 299 survivors of acute MI. Zuckerman, et al 4) reported that the rates of thromboembolic events and myocardial reinfarction in patients with acute MI were significantly higher in aCL-positive patients than in the aCL negative group.…”
Section: Discussionsupporting
confidence: 85%
“…However, there have been many studies on myocardial infarction and coronary artery disease (CAD) in which the frequency of elevated aCL antibodies was not predictive of subsequent cardiovascular complications. 5) The importance of serum aCL levels in the natural history and prognosis of acute coronary syndrome (ACS) is still undetermined. In the present study, we evaluated the association of aCL antibodies with reccurent cardiac events in patients with acute coronary syndrome (ACS).…”
mentioning
confidence: 99%
“…Coronary artery bypass graft failure has also been reported in patients with elevated ACA [11], Thus, it has been sug gested that ACA appears as an immune re sponse to myocardial injury and serves as a predictor of subsequent thrombotic events. Some investigators have recommended anti coagulation, antiplatelet or immunosuppres sive therapy in patients with high ACA levels and previous thrombotic events [10,11,14], Our data are in agreement with two recent clinical trials [15,16] that found no associa tion between elevated ACA and the severity of coronary disease or clinical outcome in acute coronary syndromes. In addition we and others [10,16] have found that ACA-pos itive patients with coronary disease have identical coronary risk factor profiles to pa tients without ACA.…”
Section: Discussionsupporting
confidence: 82%
“…Some investigators have recommended anti coagulation, antiplatelet or immunosuppres sive therapy in patients with high ACA levels and previous thrombotic events [10,11,14], Our data are in agreement with two recent clinical trials [15,16] that found no associa tion between elevated ACA and the severity of coronary disease or clinical outcome in acute coronary syndromes. In addition we and others [10,16] have found that ACA-pos itive patients with coronary disease have identical coronary risk factor profiles to pa tients without ACA. We also observed no dif ference in the complexity of coronary stenoses or the presence of intracoronary thrombus when comparing angiograms of ACA-positive and ACA-negative patients.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, some authors 3,10 have found that aPL antibodies after MI are a risk factor for recurrent events, although these results have not been verified by others 11,12 . In addition, anticardiolipin antibodies in healthy men have been shown to confer a twofold increased relative risk for MI 2 .…”
Section: Discussionmentioning
confidence: 89%